Vermicompost application to improve soil physicochemical properties and organic choy sum yield - Masri, Intan Nadhirah (2021)
Land degradation and agricultural waste management are worsened by unsustainable farming practices that are only concerned with boosting yields. Under the organic farming system, agricultural waste was transformed into soil amendment products via vermicomposting due to the ability of the process to convert most green waste into a good quality amendment product in a short duration of time. The farming system used soil amendment to recover the physicochemical properties of degraded soil. However, in Malaysia, limited studies evaluate the potential of leguminous leaf trimmings as a source of feedstock and scrap office paper with yard compost as bulking material in vermicomposting. Therefore, a study was conducted to i) produce vermicompost from Gliricidia sepium trimming residue, scrap office paper and yard compost; ii) investigate the effect of the produced vermicompost on the physicochemical properties of potting soil at different ratios as a potting media of an organically grown choy sum mustard; iii) establish the optimum mixing ratio of vermicompost and potting soil for a maximum yield of organic choy sum mustard. The vermicomposting process was carried out according to the conventional vermi pit method, where Eudrillus eugeniae was utilised as the worm species. According to selected standards, the quality of the product and the potting mixtures were determined through standard chemical and physical analysis methods. The potting mixtures trials adopted a completely randomised design with three replications and six different potting mixture ratios treatments (Tl-20:80, T2-40:60, T3-60:40, T4-80:20, TS-100: 0 and T6-0: 100). The quality of organic choy sum mustard harvested was characterised according to FAMA: FS020-2001 standard. Results showed that the vermicompost produced from the study followed the required parameters according to MS 1517 and other international standards and significantly improved the choy sum mustard yield by more than 200% compared to control. In addition, the majority of the potting soil physicochemical properties were also significantly elevated by mixing with 60% vermicompost. In conclusion, it was viable to vermicompost waste materials such as leguminous leaf residue and scrap office paper with yard compost. The vermicompost product was able to improve degraded soil and provide sufficient nutrients for leafy vegetable growth.